ANALISIS MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (K–3) PADA BAGIAN PRESSING DI PT. X - Elfitria Wiratmani (LPPM, 2010)
The purpose of the study is to analyze the management of occupational safety and health in order to reduce the high accident rate in the pressing. This research was conducted at PT. X, Tambun Bekasi. This method of using survey methods / observations directly by taking data from the company's data on the number of accidents occurred during the last 3-years and conduct interviews to determine the causes of the accident. Data analysis technique used is to use pareto chart that aims to determine the level of most major accidents occur, then the causal diagram to determine the root cause of the accident, and the 5W +1 H is a troubleshooting step.The data show that in 2006-2008 the accident occurred 45 times in the pressing, a lot of accidents happening is sandwiched ie 20 times (44.4%), the second highest accident was hit by fragments 9 times as much material (20.0%), The third highest accident-hit material that is as much as 7 times (15.6%), the second highest accident slip that is counted 5 times (11.1%) and injuries that occur at least that is pierced 4 times (8.9%). After the authors analyze the occurrence of workplace accidents through the analysis of Pareto diagrams, cause and effect diagrams. Occupational accidents that occurred due to the operator because of insufficient understanding of the workings of the machine, less careful in work, paying less attention to personal protection and lack of follow work rules, as for other causes of the condition of old machines and lack of maintenance. Keywords : management of occupational safety and health